Variability of Tear Osmolarity Measurements With a Point-of-Care System in Healthy Subjects-Systematic Review - Baenninger, Philipp B; Voegeli, Susanne; Bachmann, Lucas M; Faes, Livia; Iselin, Katja; Kaufmann, Claude; Thiel, Michael A (Cornea, 2018)
To assess the variability of osmolarity measured by the point-of-care TearLab system in healthy eyes. A systematic review was performed by searching MEDLINE, Scopus, and the Web of Science Databases until November 2016 and checking reference lists of included articles and reviews. The requirements for inclusion were the availability of TearLab results in healthy subjects and a minimum study sample of 20 eyes. Two reviewers assessed articles against the inclusion criteria, extracted relevant data, and examined the methodological quality. We computed the weighted mean osmolarity using the study size as the weighting factor and calculated the rate of subjects with osmolarity values >308 mOsm/L, the Dry Eye Workshop Report 2017 (DEWS) cut-off value for dry eye disease (DED). We repeated the analysis after excluding reports with a possible conflict of interest or missing description of subject selection. Searches retrieved 105 nonduplicate articles, and we included 33 studies investigating 1362 eyes of healthy participants who were asymptomatic and showed no clinical signs of DED. Sixty-three percent were female, and mean age was 37.3 years (range: 21.5-69.0 yr). Weighted mean osmolarity was 298 mOsm/L (95% confidence interval, 282-321 mOsm/L). The result of the subgroup analysis was similar. Overall, 386 of 1362 eyes (28.3%) fulfilled the DEWS's definition of DED (>308 mOsm/L). There is a high variability of osmolarity measurements with the TearLab system. A substantial number of healthy subjects fulfill the DEWS's definition of DED. We propose interpreting the TearLab osmolarity results cautiously and in the context of other established methods.